Law No . 4 of the year 2018 on amending some provisions of the law on Joint Stock companies, Partnerships limited by shares and limited liability companies, Promulgated by law No. 159 of the year 1981 / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 2/2018